A highly selective and sensitive photoinduced electron transfer (PET) based HOCl fluorescent probe in water and its endogenous imaging in living cells - Liang, Lijuan; Liu, Chang; Jiao, Xiaojie; Zhao, Liancheng; Zeng, Xianshun (Chemical communications (Cambridge, England), 2016)
A probe based on the phenothiazine-acridine orange conjugate (Ptz-AO) has been designed and synthesized for the sensitive and selective detection of HOCl. Ptz-AO has excellent properties, including pH-independence of fluorescence, high resistance to photobleaching, and response in real time. The value of Ptz-AO was confirmed by exogenous, endogenous and the real-time imaging of HOCl in vitro using a fluorescence microscope. A probe based on the phenothiazine-acridine orange conjugate (Ptz-AO) has been designed and synthesized for the sensitive and selective detection of HOCl.